Perception of university students on unwanted pregnancy in South West Nigeria / Olukunmi ‘Lanre Olaitan - Olaitan, Olukunmi ‘Lanre (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2018)
This study investigated the perception of unwanted pregnancy among university students in South West Nigeria. A cross-sectional survey was conducted and data were analyzed on perception of unwanted pregnancy. The variables examined include, perception of the causes consequences and prevention of unwanted pregnancy. A multi-stage sampling technique was used to select 400 subjects and a structured questionnaire was used to collect data from the respondents. The findings revealed that all the three null-hypotheses generated were rejected, using Chi-square (X2) statistical method at  = 0.05 level of significance. The findings showed that university students have significant perception of the causes, consequences and prevention of unwanted pregnancy. Based on the findings, recommendations were made such as: parent should give sufficient fund to their children; introduction and teaching of sex-education should be included in the school curriculum; adequate and functioning of family planning programs/clinics should be established in schools amongst others.